2004
DOI: 10.1016/j.csr.2003.10.006
|View full text |Cite
|
Sign up to set email alerts
|

A mechanical energy budget for the North Sea

Abstract: A three-dimensional baroclinic numerical model is used to quantify the components of the mechanical energy budget for a semi-enclosed sea, the North Sea. As anticipated, tidal energy is the largest supplier of mechanical energy to the North Sea. Although the energy supply due to winds is responsible for the seasonal variations occurring in the budget, it is one order of magnitude smaller than that due to tides. Most of the input tidal energy is dissipated, specifically in the shallow southern region. Estimates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…One pioneering effort by Taylor (1919) was based on energy-budget considerations for the Irish Sea, where the net deficit of the energy was attributed to the dissipation due to the bottom friction. Tidal models have been developed for understanding the tidal energy flux and dissipation in recent years (Davies et al, 2004;Barthel et al, 2004;Seim et al, 2006;Abdennadher and Boukthir, 2006;Foreman et al, 2006;Zhong and Li, 2006;. For example, Barthel et al (2004) used a 3-D baroclinic model to quantify the components of the mechanical energy budget; they found that most of the input tidal energy are dissipated in the shallow region.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…One pioneering effort by Taylor (1919) was based on energy-budget considerations for the Irish Sea, where the net deficit of the energy was attributed to the dissipation due to the bottom friction. Tidal models have been developed for understanding the tidal energy flux and dissipation in recent years (Davies et al, 2004;Barthel et al, 2004;Seim et al, 2006;Abdennadher and Boukthir, 2006;Foreman et al, 2006;Zhong and Li, 2006;. For example, Barthel et al (2004) used a 3-D baroclinic model to quantify the components of the mechanical energy budget; they found that most of the input tidal energy are dissipated in the shallow region.…”
mentioning
confidence: 98%
“…Tidal models have been developed for understanding the tidal energy flux and dissipation in recent years (Davies et al, 2004;Barthel et al, 2004;Seim et al, 2006;Abdennadher and Boukthir, 2006;Foreman et al, 2006;Zhong and Li, 2006;. For example, Barthel et al (2004) used a 3-D baroclinic model to quantify the components of the mechanical energy budget; they found that most of the input tidal energy are dissipated in the shallow region. Seim et al (2006) estimated the tidal energy dissipation rates from the divergence of the energy flux in a shallow, sinuous estuary.…”
mentioning
confidence: 98%